Surface plasmon-enhanced fluorescence on Au nanohole array for prostate-specific antigen detection - Zhang Q (Dove Medical Press, 2017)
Qingwen Zhang,1,2,* Lin Wu,3,* Ten It Wong,4 Jinling Zhang,5 Xiaohu Liu,5 Xiaodong Zhou,4 Ping Bai,3 Bo Liedberg,5 Yi Wang1,2,5 1School of Ophthalmology and Optometry, Eye Hospital, School of Biomedical Engineering, Wenzhou Medical University, 2Wenzhou Institute of Biomaterials and Engineering, Chinese Academy of Sciences, Wenzhou, People’s Republic of China; 3Electronics and Photonics Department, Institute of High Performance Computing, 4Institute of Materials Research and Engineering, Agency for Science, Technology and Research (A*STAR), 5Centre for Biomimetic Sensor Science, School of Materials Science and Engineering, Nanyang Technological University, Singapore *These authors contributed equally to this work Abstract: Localized surface plasmon (LSP) has been widely applied for the enhancement of fluorescence emission for biosensing owing to its potential for strong field enhancement. However, due to its small penetration depth, LSP offers limited fluorescence enhancement over a whole sensor chip and, therefore, insufficient sensitivity for the detection of biomolecules, especially large molecules. We demonstrate the simultaneous excitation of LSP and propagating surface plasmon (PSP) on an Au nanohole array under Kretschmann configuration for the detection of prostate-specific antigen with a sandwich immunoassay. The proposed method combines the advantages of high field enhancement by LSP and large surface area probed by PSP field. The simulated results indicated that a maximum enhancement of electric field intensity up to 1,600 times can be achieved under the simultaneous excitation of LSP and PSP modes. The sandwich assay of PSA carried out on gold nanohole array substrate showed a limit of detection of 140 fM supporting coexcitation of LSP and PSP modes. The limit of detection was approximately sevenfold lower than that when only LSP was resonantly excited on the same substrate. The results of this study demonstrate high fluorescence enhancement through the coexcitation of LSP and PSP modes and pave a way for its implementation as a highly sensitive bioassay. Keywords: gold nanohole array, localized surface plasmon, propagating surface plasmon, fluorescence enhancement, prostate-specific antigen